INTEGRASI SWOT KUANTITATIF DAN KUALITATIF UNTUK MENYUSUN PERENCANAAN STRATEGIS BIDANG PENDIDIKAN (Studi Kasus Di Eks-Jurusan PendidikanOlahragaDan Kesehatan (JPOK) Dan Eks-JurusanIlmuPendidikan FKIP UNS Surakarta) - Husain Musthofa; Suharno Suharno; Yuyun Estriyanto (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2020)
This study aims to determine (1) the position of the quadrant in each study program in the Ex-POK Department and the Ex-Department of Education using a SWOT analysis (2) (Strength Weakness Opportunity Threath) to plan strategic planning for the ex-POK and ex Department of Education as an effort to improve the quality of education. This study uses a quantitative qualitative approach with a population consisting of lecturers, students, and alumni of the last five years in each study program. The sampling technique uses purpose sampling. Data collection uses questionnaires / quisioners, observation and documentation. Data analysis using flow model techniques. The results showed that the Primary School Teacher Education Program, Guidance and Counseling and Physical Education, Health and Recreation Education were in quadrant I using a progressive planning strategy in the three study programs based on the results of the SWOT analysis: (1) HR capacity improvement. (2) Making the student achievement program (the most outstanding student) a superior program for students. (3) Implement curriculum in a disciplined and responsible manner. (4) Increasing international journal publications for elementary school teacher education study program lecturers. (5) Periodically improve maintenance of infrastructure. (6) Conduct an analysis of budget requirements to draft a budget. (7) Applying work based learning in student learning. (8) Develop a clear SOP for the study program management organization. (9) Improve communication between universities and the world of work. (10) Improve the performance of the multimedia team and information in the study program. (11) Improving cooperative relations with partner institutions. (12) Establish cooperation with the government in the regions to distribute study program graduates.